Sildenafil as a vasodilatatory madiator in the treatment of abdominal sepsis - Carvalho, Marília Daniela Ferreira; Silvestre, Ingrid Tinôco; Risuenho, Amanda Jayne Guedes; Rêgo, Amália Cínthia Meneses; Araújo-Filho, Irami; Azevedo, Ítalo Medeiros; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2012)